Determining the C60 molecular arrangement in thin films by means of X-ray diffraction - Elschner, C; Levin, A; Wilde, L; Grenzer, J; Schroer, C; Leo, K; Riede, M (International Union of Crystallography, 2011)
The electrical and optical properties of molecular thin films are widely used, for instance in organic electronics, and depend strongly on the molecular arrangement of the organic layers. It is shown here how atomic structural information can be obtained from molecular films without further knowledge of the single-crystal structure. C60 fullerene was chosen as a representative test material. A 250 nm C60 film was investigated by grazing-incidence X-ray diffraction and the data compared with a Bragg-Brentano X-ray diffraction measurement of the corresponding C60 powder. The diffraction patterns of both powder and film were used to calculate the pair distribution function (PDF), which allowed an investigation of the short-range order of the structures. With the help of the PDF, a structure model for the C60 molecular arrangement was determined for both C60 powder and thin film. The results agree very well with a classical whole-pattern fitting approach for the C60 diffraction patterns. © 2011 International Union of Crystallography.